2015
DOI: 10.1007/s10758-015-9258-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Versus Non-academic Emerging Adult College Student Technology Use

Abstract: Emerging adult college students have developmental and educational needs which are unique to their phase of life. Emerging adults are also increasingly identified by their technology use and practices. Collegiate instructors will be better equipped for educating these individuals when armed with insights concerning emerging adults' technology related practices. The purpose of this study is to examine academic and nonacademic technology use by emerging adult college students. Survey results (N = 235) provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Email is perceived as more efficient when solving academic issues (Vrocharidou & Efthymiou, 2012); therefore, it is used more often (Dahlstrom et al, 2013). Social applications, such as Facebook, are relegated almost exclusively to non-academic purposes (Swanson & Walker, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Email is perceived as more efficient when solving academic issues (Vrocharidou & Efthymiou, 2012); therefore, it is used more often (Dahlstrom et al, 2013). Social applications, such as Facebook, are relegated almost exclusively to non-academic purposes (Swanson & Walker, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We, therefore, consider both to form a uniform group with psychotherapeutic training as the common factor (in Switzerland) [27][28][29]. In addition, the similarities between psychologists and psychiatrists, regarding educational level and awareness of relevant research, should also be taken into account [30].…”
Section: Discussionmentioning
confidence: 99%
“…For making further decisions regarding the introduction of technology, higher authorities should provide the necessary support to the students as it is essential to consider the available technological practices and environment for learning purposes (Dahlstrem & Bichsel, 2014). Gosper, Malfroy and McKenzie (2013), Dahlstrom and Bichsel (2016), Swanson and Walker (2015) have also reported that the technologies are incorporated for both academic and non-academic purposes but in a different manner. For instance, e-mail in the USA is generally preferred for non-academic purposes while social media networking for academic purposes (Swanson & Walker, 2015).…”
Section: Technology In Educational Settingmentioning
confidence: 99%
“…Gosper, Malfroy and McKenzie (2013), Dahlstrom and Bichsel (2016), Swanson and Walker (2015) have also reported that the technologies are incorporated for both academic and non-academic purposes but in a different manner. For instance, e-mail in the USA is generally preferred for non-academic purposes while social media networking for academic purposes (Swanson & Walker, 2015). On the other hand, online libraries and learning management systems are considered suitable for academic purposes by the students in Australia (Gosper, Malfroy, & McKenzie, 2013).…”
Section: Technology In Educational Settingmentioning
confidence: 99%